The Effectiveness of Group Guidance Service Implementation in Improving the Comprehension of Advanced Study For Student of Ninth Graders at Junior High School of Darul Hamidin Pademara - Jamali; Ida Khaerun Nisa (RedwhitePress)
This study aims to know the effectiveness of group guidance service on understanding advanced study for student of ninth gradersat Junior High School ofDarul Hamidin Padamara in the school year 2018/2019. This study used a sample of 30 students with the control class of 15 students and the experimental class of 15 students. The instrument used to know the comprehension of students' advanced studywas a set of 30 items. While the hypothesis testing technique used was the statistical analysis test t-test.Based on the result of data analysis, the data obtained from the pre-test measurement for the control class was 657 with the average of 43.8 and the post-test measurement data was 598 with the average of 39.9 or pre-test <post-test (657 < 598) and measurement data for the experimental class 1332> 971. With t-count 9.6 and t-table 2.048 so t-count is greater than t-table then Ha is accepted and Ho is rejected. So the hypothesis states that